STRATEGI KEMITRAAN SMK DENGAN STAKEHOLDERS DALAM PENGEMBANGAN KEWIRAUSAHAAN LULUSAN - Samsudi, Samsudi; Widodo, Joko; Margunani, Margunani (Jurnal Penelitian Pendidikan, 2016)
This study aims at finding a synergetic partnership model between vocational high schools (SMK) with stakeholders for the educational implementation of SMK in developing their graduate entrepreneurship. The study employed Research and Development as research method. The first-year results of the study are as follows: (1) a synergetic and sustainable partnership between SMK and stakeholders in developing the graduate entrepreneurship is very essential mainly in the aspects of curriculum development, implementation of learning strategies, utilization of human resources, evaluation, and distribution of graduates; (2) the existing partnership between SMK and stakeholders has not specifically developed graduate entrepreneurship, but more in the form of implementation of industrial working practices (prakerin) which includes learning activities, utilization of human resources, and evaluation of learning; (3) partnership between SMK and stakeholders is very necessary, starting from the planning and development of the curriculum.